Ground movement in a moderately expansive soil subject to rainfall infiltration through pervious paving - Johnson, Timothy; Cameron, Donald; Moore, Gregory; Brien, Chris (Ecological engineering, 2020)
Pavements, rooftops and compacted soils inhibit rainfall infiltration across our cities and drains built to prevent flooding can further reduce water availability to urban ecosystems. These hydrological changes diminish the provision of ecosystem service benefits to local populations and negatively impact downstream communities and environments. Stormwater engineering can help restore infiltration, but little use has been made of infiltration systems in expansive clay soil (often referred to as reactive clay), due to the potential for problematic shrinking and swelling soil movements in response to changes in soil moisture. In an experiment in South Australia, ground movement and moisture variation were monitored in moderately reactive clay soil beneath pervious and impervious paving, revealing that soil moisture and ground movement were influenced by interactions between pavement treatment, the design of the pervious pavement’s gravel base layer, the size and proximity of trees, and the season. Where there were no tree influences, water-related ground movement was smaller near impervious paving, but ground movement was smaller near pervious paving at sites near trees. The differences in ground movement between pervious and impervious pavements were small when compared with the amplitude of ground movement observed at pervious and impervious pavement treatments between summer and winter. •soil was typically drier beneath permeable paving than impermeable paving.•infiltration marginally reduced reactive ground movement near trees.•infiltration through permeable paving into reactive clay was not problematic.•soil water extraction by trees increases infiltration capacity of clay.